Pengaruh Kompensasi terhadap Kinerja Aktivis KSP Credit Union (CU) Keling Kumang di Branch Office Sekadau - Fitria Elvi (Hunatech Vol. XXX, No. XXX, 2022)
Compensation, definitely, affects the performance of the activists. The compensation, whether sufficient or not, will affect the performance of the activists. If the compensation given is sufficient, thus the activist will have good working performance. This study aims to argue the effect of the compensation variable on the performance of KSP CU Keling Kumang activists. Based on the previous research, enriched with supporting theories proposed by the experts using the SPSS program as a statistical data processing tool. The type of the research is descriptive and qualitative. In this study, the researcher used a questionnaire as a data collection tool and then processed it using a Simple Linear Regression analysis tool to prove that compensation indeed affect the performance of KSP CU Keling Kumang activists at Branch Office Sekadau and the results from the regression equation Y = 40,972 + 0.136 X.